(untitled) (Journal of Asian Development Studies, 2024)
This study examines the depiction of gender in Pakistani and American television discussion programmes. The primary objective is to determine if the talk shows in both countries (i.e., Pakistan and America) display typical gender stereotypes or whether they challenge dominant views of gender and promote fresh depictions. To accomplish this objective, content analysis is performed to examine the sample comprising Pakistani and American television talk programmes. Specifically, programmes broadcast on Pakistani and American general-interest networks have been chosen. Results indicate that only individuals with binary gender expressions (female and male) participated. Males are likelier to play a prominent role in these programmes, particularly as the host position, which is essential to the format’s dynamics. As a rule, female characters are less powerful and use significantly less humour than their male counterparts in these talk shows in Pakistan and the United States. On the other hand, late-night talk shows are known for their inclusivity in featuring both male and female guests. They are open to discussing a wide range of topics, from intimate and political matters to current affairs and private issues, without gender bias. The primary conclusion of this study that can be reached is still problematic in terms of gender (male and female) representation, mainly owing to the absence of female players in dominating positions and the preconceived notions about women when they do humour as a host of the programme.